The UJI EFEKTIFITAS GEL KOMBINASI EKSTRAK DAUN BELUNTAS (Pluchea indica L. Less) DAN RIMPANG JAHE MERAH (Zingiber officinale Roscoe) TERHADAP BAKTERI Propionibacterium acne DAN Staphilococcus epidermidis - Mindiya Fatmi; Agung Eru Wibowo; Deni Rahmat (Jurnal Insan Farmasi Indonesia, 2022)
Beluntas leaf (Pluchea indica L. Less) and red ginger rhizome (Zingiber officinale Roscoe) is a plan have activity as antibacterial causes acne. Beluntas leaf contain antibacterial compounds from alkaloid, flavonoid free type flavonol, steroid and tannin. Red ginger rhizome extract compounds flavonoid, essential oil, polifenol, and saponin. This study aim to develop gel product extract combination from beluntas extract and red ginger rhizome at concentration 1: 1; 1: 2 and 3:2 formulated in gel, then tested the physical characteristic and gel microbiology tested on P. acne and S. epidermidis. Beluntas leaf and red ginger rhizome extracted by maceration in ethanol 96%, and carbopol 934 as gel base. Physical characteristic test comprise homogeneity, organoleptic, pH, dispersion gel and viscosity. Microbiology tested use method diameter of inhibition zone with Medi-Klin GelÂ® as positive control. The result show homogeneous gel preparation, with brownish green color, ginger smell, pH 5,83-6,07, spreadability 5,1-5,7 cm, viscosity 690000 cp-1460800 cp. effect of adding extract beluntas leaf and red ginger rhizome to gel preparation, in both single and combination extracts. Antibacterial evaluation showed that formula 3 give the best effectiveness with 5,92 mm zone of inhibition against P. acnes and 4,15 mm against S. epidermidis.